Pengaruh Pendekatan Saintifik terhadap Kemampuan Pengukuran pada Anak Usia Dini di TK YWKA Palembang - Suci Indah Kenedi (EduInovasi: Journal of Basic Educational Studies, 2026)
This study aims to analyze the influence of a scientific approach on the measurement skills of 5–6-year-old children at YWKA Kindergarten in Palembang. The background of this study stems from the limited ability of children to distinguish sizes, compare objects, and use standard and non-standard measuring tools consistently. The scientific approach is considered relevant to address these problems because it provides opportunities for children to observe, ask questions, try, reason, and communicate results systematically and based on direct experience. This study used a quantitative method with a simple experimental design. The study population was all children in group B, while the sample was determined using a purposive sampling technique. Data collection was carried out through observation and questionnaires compiled based on measurement ability indicators, then tested for validity and reliability before use. Data analysis was carried out using prerequisite tests and hypothesis tests with the help of SPSS software. The results showed that the scientific approach had a significant effect on children's measurement skills, indicated by an increase in the ability to understand the length, volume, and mass of objects after the application of the approach. These findings confirm that scientific activity-based learning can provide concrete experiences that strengthen children's quantitative understanding. Thus, the scientific approach can be used as an effective learning strategy to develop measurement skills in early childhood.